Electronic commerce as an introduction to the transformation of the knowledge economy – A field study on small projects in the Kingdom of Saudi Arabia – - Faid, Abeer Asaid (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to identify a shift from an oil economy to a knowledge economy by using electronic commerce for small projects, which is what the vision of the Kingdom 2030 seeks. However, small projects suffer from the inability to market in a way that allows them to succeed and advance the national economy, and to enter into global competition. The study was prepared to clarify the role of e-commerce for small enterprises in this transformation.The study relied on the descriptive-analytical approach and the distribution of a questionnaire to collect primary data and statistically analyze it, in which some of the statistical methods used in the SPSS program were used.The study concluded that electronic commerce is able to achieve marketing opportunities for small projects, and that small projects need to re-engineer their marketing operations (especially the marketing mix) in order to be able to apply electronic commerce, and indicated that electronic commerce is able to transform into a knowledge economy.A set of recommendations was proposed to activate e-commerce for small projects, including providing financial support, attention to bringing and training skilled workers trained in the proper application of e-commerce technology, re-engineering the marketing mix in a manner that allows the proper application of electronic commerce.
Keywords: e-commerce; knowledge economy; small projects; re-engineering of marketing operations